Six2 defines and regulates a multipotent self-renewing nephron progenitor population throughout mammalian kidney development - Kobayashi, Akio (2008)
Nephrons, the basic functional units of the kidney, are generated repetitively during kidney organogenesis from a mesenchymal progenitor population. Which cells within this pool give rise to nephrons and how multiple nephron lineages form during this protracted developmental process is unclear. We demonstrate that the Six2-expressing cap mesenchyme represents a multipotent nephron progenitor population. Six2-expressing cells give rise to all cell-types of the main body of the nephron, during all stages of nephrogenesis. Pulse labeling of Six2-expressing nephron progenitors at the onset of kidney development suggests that the Six2-expressing population is maintained by self-renewal. Clonal analysis indicates that at least some Six2-expressing cells are multipotent, contributing to multiple domains of the nephron. Furthermore, Six2 functions cell-autonomously to maintain a progenitor cell status, as cap mesenchyme cells lacking Six2 activity contribute to ectopic nephron tubules, a mechanism dependent on a Wnt9b inductive signal. Taken together, our observations suggest that Six2 activity cell-autonomously regulates a multipotent nephron progenitor population.